THE RELATIONSHIP BETWEEN JOB SATISFACTION, MOONLIGHTING INTENTIONS, TURNOVER INTENTION AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR: A LITERATURE REVIEW - Santoso Santoso; Marinus Tukiran; Peni AW; Ika Pratiwi; Roosganda Elizabeth; Ratu Erlina Gentari (Yayasan Education and Social Center, 2023)
Research on the complex and multifaceted relationship between job satisfaction, moonlighting intentions, turnover intentions, and organizational citizenship behaviour has been conducted in organizational behaviour. Researchers have investigated various factors contributing to positive organizational citizenship behaviour, job satisfaction, moonlighting, and turnover intentions. This study aims to examine the interrelationships between Job Satisfaction, Moonlighting Intentions, Turnover Intention, and Organizational Citizenship Behavior and their impact on an organization's success. Organizations can create a positive work environment that fosters employee well-being, engagement, and productivity when they thoroughly understand the complex interplay among these factors. This results in improved outcomes for employees as well as the organization. The research employs a qualitative methodology, utilizing a literature review that begins with a meticulous selection of relevant topics and keywords to identify appropriate journals and sources. This process is crucial as it guarantees that the information collected is accurate, relevant, and up-to-date. By selecting appropriate topics and keywords, researchers can ensure that they gather the most pertinent and reliable information for their study. According to the study, there is a negative correlation between job satisfaction and moonlighting intentions among IT professionals. It implies that those who are content with their current job are less inclined to seek additional employment. Additionally, the study revealed that job satisfaction and organizational commitment significantly negatively impact turnover intention. Therefore, organizations can decrease turnover intention by enhancing job satisfaction, organizational commitment, and person-organization fit. Furthermore, the study found that job satisfaction positively and significantly influences organizational citizenship behaviour. Moreover, organizational commitment mediates the relationship between job satisfaction and organizational citizenship behaviour positively and significantly